Postmodern apocalypse in White Noise and London Fields - Khodadadegan, Neda; Jujar Singh, Hardev Kaur; Babaee, Ruzbeh (Australian International Academic Centre, 2016)
Postmodern Apocalypse is considered as a strategy a writer employs to depict the dreadfulness of nuclear disaster. It is a rich way of transmitting ideas of catastrophe and fear into a more meaningful fiction about a teleological end. This study analyzes postmodern apocalypse in two selected novels, namely Don DeLillo’s White Noise (1985) and Martin Amis’s London Fields (1989). The term which refers to characters who cry their concern about the destruction of the world demonstrates a sense of apocalypse in a community of nuclear age. Both DeLillo and Amis show their fear of a nuclear explosion. The present study aims to present an apocalyptic reading of two selected texts through using in the 1980s.Elizabeth K. Rosen’s Apocalyptic Transformation: Apocalypse and the Postmodern Imagination (2008).